Middle East Experience With Transanal Endoscopic Microsurgery (TEM) - Seyed Vahid Hosseini Hosseini (Shiraz University of Medical Sciences, 2014)
conditions. Big deal of this procedure is avoiding of open abdominal surgeries or better exposure in transanal approches.Objectives: The purpose of this study was to present a single institutional experience in Shiraz, Iran regarding the application of Transanal Endoscopic Microsurgery (TEM). To our knowledge this is the first report from the Middle East.Patients and Methods: Between 2009 and 2012, thirty patients underwent TEM in our center. We assessed complications and recurrence rate. Patients with fewer than six months of follow-up were excluded.Results: Patients included 17 men and 13 women with a mean age of 44.4 years (ranged 17-80). The mean tumor distance from the anal verge was 9.8 cm. One patient with adenomatous polyp experienced recurrence 14 months postoperatively. Regarding procedure-related complications, one case developed hemorrhage and another case fever and infection in the site of operation. Two patients experienced incontinence for about 3 weeks after TEM surgery.Conclusions: Considering the cultural and religious context of the Middle East, we recommend TEM procedure in specialized centers in this region of the world.